2012
DOI: 10.3945/an.112.002303
|View full text |Cite
|
Sign up to set email alerts
|

Chemopreventive Properties of Dietary Rice Bran: Current Status and Future Prospects

Abstract: Emerging evidence suggests that dietary rice bran may exert beneficial effects against several types of cancer, such as breast, lung, liver, and colorectal cancer. The chemopreventive potential has been related to the bioactive phytochemicals present in the bran portion of the rice such as ferulic acid, tricin, β-sitosterol, γ-oryzanol, tocotrienols/tocopherols, and phytic acid. Studies have shown that the anticancer effects of the rice bran-derived bioactive components are mediated through their ability to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
144
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 184 publications
(171 citation statements)
references
References 92 publications
5
144
1
9
Order By: Relevance
“…Here, we report for the first time that γ-oryzanol reduced MDA-MB-231 cell invasion, which corresponded with the finding that Hex and DCM fractions reduced cancer cell invasion. On the other hand, several studies have reported that γ-tocotrienol showed anti-tumor effects, as well as the potential to induce apoptosis, and to inhibit angiogenesis and metastasis (Henderson et al, 2012;Manu et al, 2012). Our results confirm that at 10 μg/ml of γ-tocotrienol reduced MDA-MB-231 cell invasion.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Here, we report for the first time that γ-oryzanol reduced MDA-MB-231 cell invasion, which corresponded with the finding that Hex and DCM fractions reduced cancer cell invasion. On the other hand, several studies have reported that γ-tocotrienol showed anti-tumor effects, as well as the potential to induce apoptosis, and to inhibit angiogenesis and metastasis (Henderson et al, 2012;Manu et al, 2012). Our results confirm that at 10 μg/ml of γ-tocotrienol reduced MDA-MB-231 cell invasion.…”
Section: Discussionsupporting
confidence: 81%
“…Gamma oryzanol is a mixture of phytosteryl ferulates found in rice bran. It is particularly important to note that γ-oryzanol exhibits antioxidant, anti-carcinogenesis and anti-inflammatory properties (Henderson et al, 2012;Klongpityapong et al, 2013). Here, we report for the first time that γ-oryzanol reduced MDA-MB-231 cell invasion, which corresponded with the finding that Hex and DCM fractions reduced cancer cell invasion.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Polyphenols affect cancer by inhibiting cyclooxygenase, DNA topoisomerase, and DNA methylation, inducing phase II detoxification, and influencing cell signaling [25,26]. Polyphenols include cocoa, curcumin (found in turmeric), rice bran oil phenolics, caffeic acid, ferulic acid, and ferulic acid esters [45].…”
Section: Phenolsmentioning
confidence: 99%
“…Phytic Acids: Phytic acids include defatted rice bran phytate and inositols [45]. Inositols include inositol phophates, inositol hexakisphosphate (InsP6), and myo-Inositol [67].…”
Section: Phenolsmentioning
confidence: 99%